17.2k views
0 votes
What is equivalent to 4(2x+6)=3(x-2)

User Zsuzsa
by
5.6k points

2 Answers

6 votes

Answer: x = -6

Explanation:

(4)(2x)+(4)(6)=(3)(x)+(3)(−2) (Distribute)

8x+24=3x+−6

8x+24=3x−6

Step 2: Subtract 3x from both sides.

8x+24−3x=3x−6−3x

5x+24=−6

Step 3: Subtract 24 from both sides.

5x+24−24=−6−24

5x=−30

Step 4: Divide both sides by 5.

5x /5 =5/−30

x=−6

User Anurag Sundaram
by
7.0k points
4 votes

Answer:

x=-6

Explanation:

4(2x+6)=3(x-2)

8x+24=3x-6

-24= -24

8x=3x-30

-3x =-3x-30

5x = -30

-- ----

5 5

x= -6

User Leon Joosse
by
5.8k points